Study of antioxidants from herbal plant extracts in vitro - Eka Susanti HP; Novi Elisa; Novi - Elisa; Arina Zulfah Primananda; Yustisia Dian Advistasari (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Abstract Background : Antioxidants are substances that can prevent the formation of free radical reactions, people in Indonesia use a lot of natural ingredients as traditional medicine, one of which as antioxidants for free radical handling . Free radicals are compounds or molecules that contain one or more unpaired electrons in its outer orbitals. The presence of unpaired electrons causes these compounds to be very reactive looking for partners, by attacking and binding electrons around them so that they can trigger disease. Destination : The purpose of this study was to discuss the antioxidant activity of wormwood, neem, cinnamon, brotowali plants in vitro. Method : The method that can be used in antioxidant test research was the DPPH method in vitro through effective concentration (EC50), identification of phytochemical screening of each extract, and total flavonoid test. Results : The results of the study obtained phytochemical screening of wormwood, neem, cinnamon, brotowali extracts contained secondary metabolites in the form of flavonoids, tannins, saponins, steroids and triterpenoids which have a role as antioxidanttest. Total flavonoid test of wormwood extract had the largest total flavonoid content (110.353 Â± 0.802). The antioxidant test results of each cinnamon extract was 75 ppm, neem extract was 81 ppm, wormwood extract was 479 ppm, brotowali extract was 304 ppm. These results indicated that the effective antioxidant extract was cinnamon extract.